Tools selection criteria in software-developing Small and Medium Enterprises - Rivas, Lornel (2010)
Nowadays,it's well-known that Small and Medium Enterprises (SMEs) generate important contributions to the software industry. Their particular characteristics constitute a challenge to decision makers when selecting technologies, like Software Engineering Tools (SETs). Deciding in which SET to invest requires managing limited resources as well as productivity pressures. Additionally, changes in SETs also affect the selection process. This article proposes a set of criteria, which were formulated with support on the Goal Question Metric approach and considered standards like ISO/IEC 14102 and IEEE 1209, to support SMEs in the selection of SETs. These criteria were also applied to three SETs, including both commercial and open-source, to obtain a set of opportunities for supporting software engineering areas, such as project management and software development process. This proposal is aimed at forming the basis to establish a SETs selection model for SMEs.